2022
DOI: 10.1177/17588359221133169
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like cholangiocarcinoma not associated with Epstein–Barr virus or hepatitis virus: case report and literature review of 100 reported cases

Abstract: Lymphoepithelioma-like cholangiocarcinoma (LEL-CC) is a type of lymphoepithelioma-like carcinoma (LELC) and a rare variant of primary liver tumor. Although it is uncommon and only 100 cases have been reported thus far, the number of reports has increased in recent years. LEL-CC reportedly occurs more frequently in Asian women; Epstein–Barr virus (EBV) and hepatitis viruses are both strongly associated with tumor development. Here, we describe a 76-year-old woman who exhibited LEL-CC not associated with EBV or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Most of them were in the T2-T3 stage though [ 8 , 13 ]. Some studies found that LELC in the upper respiratory tract such as the nasopharynx and salivary glands was closely related to EB virus infection [ 14 ]. However, the role the EB virus played in LELCB remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were in the T2-T3 stage though [ 8 , 13 ]. Some studies found that LELC in the upper respiratory tract such as the nasopharynx and salivary glands was closely related to EB virus infection [ 14 ]. However, the role the EB virus played in LELCB remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%